2003
DOI: 10.1213/01.ane.0000061221.23197.ce
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Technique Influences Brain Temperature, Independently of Core Temperature, During Craniotomy in Cats

Abstract: Deep barbiturate anesthesia reduced brain temperature independently of body temperature in cats and significantly more than the reduction seen with halothane anesthesia. The magnitude of temperature reduction was sufficient to account for cerebral protection by barbiturates independently of any other properties of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…In the interpretation of our data, it is important to point out that the animals were anesthetized with thiopental, and, as with barbiturate anesthetics in general, the brain metabolic rate should be reduced on the basis of studies by other investigators (38). However, several investigators (14,37) have reported that, if hypotension during deep anesthesia was avoided, the decline in metabolism was minimized. We maintained blood pressure by careful support of body temperature, intravascular fluid support, and mechanically assisted ventilation to maintain oxygenation and normocapnia in normal ranges.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the interpretation of our data, it is important to point out that the animals were anesthetized with thiopental, and, as with barbiturate anesthetics in general, the brain metabolic rate should be reduced on the basis of studies by other investigators (38). However, several investigators (14,37) have reported that, if hypotension during deep anesthesia was avoided, the decline in metabolism was minimized. We maintained blood pressure by careful support of body temperature, intravascular fluid support, and mechanically assisted ventilation to maintain oxygenation and normocapnia in normal ranges.…”
Section: Discussionmentioning
confidence: 96%
“…We maintained blood pressure by careful support of body temperature, intravascular fluid support, and mechanically assisted ventilation to maintain oxygenation and normocapnia in normal ranges. We chose thiopental over halothane because halothane anesthesia is associated with dilation of cerebral vessels through a NO mechanism linked to nNOS (14). We will demonstrate well-maintained nNOS mechanisms under thiopental anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Long TE MRSI spectra were only partially water-suppressed for post-acquisition temperature measurement requirements; this was done by decreasing the VAPOR pulse amplitude until a partially-suppressed water signal was visible throughout the VOI region. Linear and second order shims were automatically adjusted with FASTMAP (21) in a 5.8 Â 5.8 Â 5.8 voxel (which included the MRSI-VOI region), leading to waterline widths at half height of [13][14][15][16][17][18][19] Hz inside the MRSI-VOI. MRSI spectra were acquired with 2500 ms TR, 4006.41 Hz spectral width (13.34 ppm) and 2 k points in the time domain.…”
Section: In Vivo Mr Studiesmentioning
confidence: 99%
“…Samples were cut into small pieces with a scalpel, inserted into a pre-weighted HR-MAS microrotor (HZ05538 BL4; 12 mL Teflon spacer, Cortecnet, Paris, France) and weighed: average biopsy sample content was 12.2 AE 6.4 mg. Deuterium oxide (D 2 O 99.995%, Carlo Erba Ré actifs-SDS, Val de Reuil, France) was then added and mixed inside each rotor using a 1 mL syringe (Becton-Dickinson S.A., Madrid, Spain) and the rotors were weighed again: average D 2 O content added was 10.7 AE 4.6 mg. Finally, the dissected samples were studied on a 9.4T magnet (DMX 400 MHz, Bruker BioSpin, Wissembourg, France) equipped with a 1 H- 13 C/ 31 P HR-MAS resonance probe. HR-MAS studies were carried out at room temperature and using the standard 3000 Hz spinning rate for the magnetic field strength.…”
Section: Ex Vivo Hr-mas Studiesmentioning
confidence: 99%
See 1 more Smart Citation